Physiology of the volume-sensitive/regulatory anion channel VSOR/VRAC. Part 1: from its discovery and phenotype characterization to the molecular entity identification - Yasunobu Okada (Journal of Physiological Sciences)
Abstract The volume-sensitive outwardly rectifying or volume-regulated anion channel, VSOR/VRAC, which was discovered in 1988, is expressed in most vertebrate cell types and is essentially involved in cell volume regulation after swelling and in the induction of cell death. This series of review articles describes what is already known and what remains to be uncovered about the functional and molecular properties as well as the physiological and pathophysiological roles of VSOR/VRAC. This Part 1 review article describes, from the physiological standpoint, first its discovery and significance in cell volume regulation, second its phenotypical properties, and third its molecular identification. Although the pore-forming core molecules and the volume-sensing subcomponent of VSOR/VRAC were identified as LRRC8 members and TRPM7 in 2014 and 2021, respectively, it is stressed that the identification of the molecular entity of VSOR/VRAC is still not complete enough to explain the full set of phenotypical properties.